2020
DOI: 10.3390/w12092338
|View full text |Cite
|
Sign up to set email alerts
|

A Climatic Perspective on the Impacts of Global Warming on Water Cycle of Cold Mountainous Catchments in the Tibetan Plateau: A Case Study in Yarlung Zangbo River Basin

Abstract: Global warming has a profound influence on global and regional water cycles, especially in the cold mountainous area. However, detecting and quantifying such changes are still difficult because noise and variability in observed streamflow are relatively larger than the long-term trends. In this study, the impacts of global warming on the catchment water cycles in the Yarlung Zangbo River Basin (YZRB), one of most important catchments in south of the Tibetan Plateau, are quantified using a climatic approach bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…We quantified water balance, which is composed of precipitation and evaporation, water yield, groundwater recharge, and soil water content of the entire YZB, indicating that more inflow from precipitation for the whole hydrological system will be consumed by evaporation rather than contributing to runoff, implying that rising temperatures have a greater impact on water balance than increasing precipitation in northern Himalayan. This is consistent with previous findings that global warming likely caused significant changes in the water cycle of cold mountain catchments (Xu et al, 2020). Soil water content can be used as a good indicator to evaluate the degree of dryness and wetness (Chakraborty et al, 2013;Li and Huang, 2021).…”
Section: Impacts Of Climate Change On Water Balancesupporting
confidence: 91%
“…We quantified water balance, which is composed of precipitation and evaporation, water yield, groundwater recharge, and soil water content of the entire YZB, indicating that more inflow from precipitation for the whole hydrological system will be consumed by evaporation rather than contributing to runoff, implying that rising temperatures have a greater impact on water balance than increasing precipitation in northern Himalayan. This is consistent with previous findings that global warming likely caused significant changes in the water cycle of cold mountain catchments (Xu et al, 2020). Soil water content can be used as a good indicator to evaluate the degree of dryness and wetness (Chakraborty et al, 2013;Li and Huang, 2021).…”
Section: Impacts Of Climate Change On Water Balancesupporting
confidence: 91%
“…46.0% decrease) during the period of 1997–2010. The change of annual lowest 7‐day mean flow can be used as the indicator of groundwater storage changes (Gao et al, 2015; Troch et al, 2013; Xu et al, 2020; Zhang et al, 2014). Significant declines in annual lowest 7‐day mean flow and reported groundwater level changes in published literatures are consistent with the findings in this study that SC was larger during the Millennium drought period (1997–2009) than at other times (Figure 5 and Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers also reported that the catchment groundwater level dropped significantly during the Millennium drought in southern Australia (Gao et al, 2014;Kinal & Stoneman, Petheram et al, 2011;Petrone et al, 2010). The change of annual lowest 7-day mean flow can be used as the indicator of groundwater storage changes (Gao et al, 2015;Troch et al, 2013;Xu et al, 2020;Zhang et al, 2014). Significant declines in annual lowest 7-day mean flow and reported groundwater level changes in published literatures are consistent with the findings in this study that SC was larger during the Millennium drought period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) than at other times (Figure 5 and Figure 6).…”
Section: Attribution Of Changes In Rainfall-runoff Relationshipmentioning
confidence: 99%
“…The possible impact of dams on the river flow regimes across the world varies based on the terrain, topography, ecology, and socioeconomic conditions of the region. In the climate change scenarios and impact of global warming, estimated runoff contributions to the total runoff from snow and glacier melt in the Beas at 35%, the Chenab 49%, and the Satluj 60% at present are going to increase with the increase in snow and glaciers melting [46][47][48]. Ali et al [8] suggested the wetter 17.04 ± 20.76% and 15.30 ± 20.16% increase in the annual mean precipitation in the Nathpa Jhakri (1500 MW) and Bhakra Nangal (1300 MW) big storage dams of the Satluj basin, respectively, in the near future was owing to snow and glaciers melting.…”
Section: Discussionmentioning
confidence: 99%